Effectiveness of Avocado Juice and Ambon Banana Juice Intervention to Increase the Hb Level of Pregnant Women - Fitria Hikmatul Ulya; Novita Sari; Budi Linuwih (Oksitosin : Jurnal Ilmiah Kebidanan, 2025)
Third trimester pregnant women are at risk of anaemia, which can increase the risk to the mother and fetus. Pregnant women in addition to taking Fe tablets, need to be supported by nutritional patterns that contain several intermediates for haemoglobin synthesis such as avocado/ambon banana. Avocado and banana ambon are enriched with iron which is effective in controlling iron deficiency, also contains vitamin C which helps increase iron absorption. This study was a quasi-experiment with two-group pretest-posttest. The population was anaemic pregnant women in the third trimester with a sample of 20 pregnant women. The sampling method used purposive sampling. The research instruments were SOP and observation sheet. Pregnant women consumed avocado juice or banana ambon juice once a day for 14 days. Data were obtained by measuring haemoglobin levels (Easytouch GCHb). The results showed that the average Hb level before avocado juice intervention was 9.12 g/dL and after 11.15 g/dL. The average haemoglobin level before the administration of ambon banana juice was 9.42 g/dL and after 10.78 g/dL. The effectiveness of avocado juice and ambon banana juice on increasing Hb levels in third trimester pregnant women with a ρ value of 0.025. Avocado juice increases the Hb level of pregnant women more than banana ambon juice. Anaemic pregnant women can use avocado juice or banana ambon juice to increase Hb levels.